Strategi Promosi di Perpustakaan Balai Bahasa Provinsi Sumatera Barat - Hadi, Sangri Al; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
His paper aims to obtain a description of: (1) promotion strategies in Library Balai Bahasa West Sumatra province, (2) constraint promotion in the Library Balai Bahasa of West Sumatra Province. Data were collected by means of observation and interviews with librarians at the Library Balai Bahasa ​​of West Sumatra Province. Analyzing data descriptively. Based on analysis of the discussion can be concluded that: Library Balai Bahasa of West Sumatera province in carrying out the promotion strategies have not been going well still have constraints, such strategies are: promotion expenditure strategy, the promotion mix strategies, strategy selection of promotional mix media, and ad copy strategies. Keywords: promotion strategy; constraints promotion